Study of two new configurations of the Barra-Costantini system with sunspot modelling. (5th June 2020) - Saadi, S.; Chaker, A.; Boubekri, M.
Highlights: Building Integrated Semi-transparent PV technology is used to improve the the Barra-Costantini system. The improvement of the Barra-Costantini system allows to produce heat and electricity. Internal solar gains are taken into consideration by calculating the sunspot area. The conventional Barra-Costantini system gives an air temperature of 22.9 °C, while systems with glazed semi-transparent PV and semi-transparent PV produce temperatures of 22.6 °C and 21.5 °C. The electrical efficiency of the PV glass reaches 15.6% while that of the glazed PV glass is 13.1%. Abstract: The aim of this paper is the numerical study of two new configurations of the Barra-Costantini system using building integrated semi-transparent PV technology. Each configuration is integrated into a room located in Ksar Chalala in Algeria. In the first new system, the glass of the conventional Barra-Costantini system is replaced by a PV glass panel. While in the second one, a single glass is placed in front of the PV glass panel. The thermal models of the systems are established by taking into consideration the solar gains by the calculation of the sunspot area on each one of the walls exposed to the direct solar radiation. By comparing the performance of the conventional Barra-Costantini system with that of the two proposed configurations, our results have shown that the use of the PV glass panel allows the system to produce simultaneously heat and electricity. The conventional Barra-Costantini system gives an internal air temperature of 22.9 °C, while systems with glazed semi-transparent PV and semi-transparent PV only produce temperatures of 22.6 °C and 21.5 °C, respectively. The maximum electrical efficiency of the PV glass panel is 15.6%, while that of the glazed PV glass panel is 13.1%.